Affective Stancetaking in the English Communicative Situation of Risk - Ushchyna, Valentyna (East European Journal of Psycholinguistics, 2016)
The article deals with the study of psycholinguistic and sociocognitive dynamics of stancetaking in the communicative situation of risk. The concept of risk presupposes decision making, while the process of decision making is seen here as a stancetaking on risk. A speaker’s stance includes subjective expressions of the speaker’s attitude towards the object of conversation, his mood, evaluations, perspective, knowledge, point of view and opinion. Stances are reflected at different levels of language: lexis, grammar, style, and pragmatics. The main focus of the research is on the affective component of stance as a manifold of axiological evaluation and emotional attitude of the speaker to risks. The overall theoretical framework for the study synthesizes dynamic approaches to discourse analysis, which form an interface of mind, discourse interaction and society.ReferencesБернстайн П. Против богов: укрощение риска / П. Бернстайн. – М. : ЗАО «Олимп–Бизнес», 2000. – 400 с.Bernstein, P. (2000). Protiv bogov: ukroshcheniye riska. Moscow: ZAO “Olimp-Bizness”. Изард К. Психология эмоций / К. Изард. – СПб. : Питер, 2000. – 464 с.Izard K. (2000) Psikhologiya emotsiy. SPb: Piter.Леонтьев А. Н. Деятельность. Сознание. Личность / А. Н. Леонтьев. – М. : Изд-вополит. лит-ры, 1975. – 304 с.Leontyev A. N. (1975) Deyatelnost. Soznaniye. Lichnost. – Moscow: Izdatelstvopoliticheskoy literatury.Мартинюк А. П. Словник основних термінів когнітивно-дискурсивної лінгвістики /А. П. Мартинюк. – Х. : ХНУ ім. В. І. Каразіна, 2012. – 196 с.Martynyik, A. (2012). Slovnyk osnovnykh terminiv kohnityvno-dyckursyvnoyilingvistyky. Kharkiv: V.I. Karazin KNU.Морозова О. І. Stance: позиція суб’єкта дискурсивної діяльності / О. І. Морозова //Вісн. Київ. нац. лінгвістичного ун-ту. Серія філологія. – 2011. – Т. 14. – № 1. –С. 87–93.Morozova, O. (2011). Stance: pozytsiya cub’yekta dyskursyvnoyi diyalnocti / VisnykKyyivskoho natsionalnoho linhvistychnoho universytetu. Seriya Filologiya. 14 (1). 87–93.Морозова О. І. Діяльнісний стиль мислення у лінгвістичних дослідженнях /О. І. Морозова // Вісн. Харк. нац. ун-ту ім. В. Н. Каразіна. – 2008. – № 811. – С. 41–45.Morozova, O. (2008). Diyalnisnyi styl myslennya u lingvistychnykh doslidzhennyah /Visnyk Kharkivskoho natsionalnoho universutetu imeni Karazina. #811. 41-45.Ушинский К. Д. Избранные педагогические сочинения : в 2 т. / К. Д. Ушинский. –М., 1953. – Т. 1. – 390 с.  Ushynskyj, K. (1953). Izbrannyie pedagogicheskiye sochineniya: v 2-h t. T. 1. Moscow. Ущина В. А. Позиціонування суб’єкта у дискурсивних ситуаціях ризику / В. А. Ущина //Вісн. Харк. нац. ун-ту ім. В. Н. Каразіна. Сер. „Романо-германська філологія.Методика викладання іноземних мов”. − 2012. − № 1023. − Вип. 72. − С. 77−84.Ushchyna, V. (2012). Pozytsionuvannya sub’yekta u dyskursivnyh sytuatsiyah ryzyku /Visnyk Kharkivskoho natsionalnoho universutetu imeni Karazina. Ser. “Romanogermanska filologiya. Metodyka vykladannya inozemnykh mov. # 1023. Vyp.92. 77–84.Шаховский В. И. Эмоции: долингвистика, лингвистика, лингвокультурология /В. И. Шаховский. – М. : Книж. дом «ЛИБРОКОМ», 2010. – 128 с.Shakhovski V. (2010). Emotsiyi: dolingvistika, lingvistika, lingvokulturologiya. –Moscow: Knizhn. dom “LIBROKOM”.Crystal D. The Cambridge Encyclopedia of Language. 3d Edition. – Cambridge: CUP,2010. – 516 p.Davies B. Positioning: The Discursive Production of Selves / B. Davies, R. Harré // Journalfor the Theory of Social Behavior. – № 20 (1). – 1990. – Р. 43–63.Du Bois J. The Stance Triangle / J. Du Bois // Stancetaking in Discourse / ed. byR. Englebretson. – Amsterdam : John Benjamins, 2007. – P. 139–182.Du Bois J. Taking a stance on emotion : affect, sequence, and intersubjectivity in dialogicinteraction / J. Du Bois, E. Karkkainen // Text and Talk. – 2012. – P. 433–451.Englebretson R. Stancetaking in Discourse: An Introduction / R. Englebretson // Stancetakingin Discourse: Subjectivity, Evaluation, Interaction ; ed. by R. Englebretson. – Amsterdam :John Benjamins, 2007. – P. 1–25.Harré R. The Singular Self: An Introduction to the Psychology of Personhood / Rom Harré. –London : Sage, 1998. – 192 p.Hyland K. Stance and Voice in Written Academic Genres / Ken Hyland. – London ; NewYork : Palgrave Macmillan, 2012. – 280 p.Jaffe A. Introduction: The Sociolinguistics of Stance / Alexandra Jaffe // Stance:Sociolinguistic Perspectives / ed. by A. Jaffe. – Oxford : OUP, 2009. – P. 3–28.Langlotz A. Creating Social Orientation Through Language. A socio-cognitive theory ofsituate social meaning / Andreas Langlotz. – Amsterdam, Philadelphia: John Benjamins,2015. – 366 p.Lerner J. S., Keltner D. (2001). Fear, anger, and risk. Journal of Personality and SocialPsychology, 81, 146–159.Oatley, K. Perceptions and Representations: The Theoretical Bases of Brain Research /Keith Oatley. – London ; Methuen ; New York : Free Press, 1978. – 262 р.Scherer, K. R. What are emotions? And how can they be measured? / K. R. Scherer //Social Science Information. − Vol. 44 (4). – London : Sage Publications, 2005. –P. 695–729.Schwarz-Friezel, M. (2007). Sprache und Emotion / Monika Schwarz-Friezel Monika. –Tübingen: A. Francke.Slovic, P. (2010). The Feeling of Risk / Paul Slovic. New York: Routlesge, 2010.Ushchyna, V. (2014). Stancetaking in the discourse on risk: identities construed. In:Subjectivity and Epistemicity. Corpus, Discourse, and Literary Approaches to Stance (pp.165-188), Dylan Glynn & Mette Sjölin, (Eds). Lund: Lund University Press.Vrobyova, O. (2015). Fifty Shades of Tension: The Ecology of Sense and Nonsense. In:Towards the Ecology of Human Communication. (pp. 85-100). Cambridge: CambridgeScholars Publishing.Sources Follett, K. (1992). Night Over Water. N.Y.: Penguin Books.